Preparation of Diorganomagnesium Reagents by Halogen–Lithium Exchange of Functionalized Heteroaryl Halides and Subsequent in situ Trapping with MgCl2·LiCl in Continuous Flow - Nishimura, Rodolfo Hideki Vicente; Weidmann, Niels; Knochel, Paul (Synthesis, 2020)
A halogen–lithium exchange in the presence of MgCl2·LiCl on a broad range of heterocyclic scaffolds using a commercial flow set-up with nBuLi as exchange reagent is reported. The resulting diheteroarylmagnesium species were subsequently trapped with various electrophiles, such as ketones, aldehydes, allylic bromides, or disulfides affording functionalized heterocycles. A scale-up was performed by simply increasing the run-time without further optimizations.
Keywords: heterocycles; flow chemistry; organomagnesium reagents; transmetalation; halogen–lithium exchange